Patterns of reef fish taxonomic and functional diversity in the Eastern Tropical Pacific - Dubuc, Alexia (2023)
A core challenge in ecology is identifying the factors that determine species distribution and functional diversity of species assemblages. Reef fish are the most diverse group of vertebrates, form taxonomically rich and functionally diverse communities and represent a key source of food for humans. We examine regional distribution patterns of reef fish species richness and functional diversity and investigate how these are determined by historical, biogeographic, energetic, and anthropogenic factors. We compiled data from 3,312 underwater visual censuses performed at 122 locations comprising rocky and coral reefs along the Eastern Tropical Pacific (ETP). We used generalized linear mixed-effects models (GLMMs) implemented in a Bayesian framework to investigate whether distance from quaternary refugia, distance from mainland, shelf area, primary productivity, sea surface temperature (SST), human population gravity, and conservation status influence reef fish species richness and functional diversity in the ETP. Species richness and functional richness (FRic) peaked towards the center of the ETP and our null model suggests that FRic followed a spatial pattern that would be predicted by species richness. Additionally, functional evenness (FEve) was highest at higher latitudes whereas functional dispersion (FDis) was homogeneous throughout the ETP. Species richness was negatively influenced by shelf area and distance from mainland, but positively influenced by SST and conservation status. FEve was influenced by human population gravity and FDis by shelf area. Reef fish species richness and functional diversity in the ETP exhibited a strong division within the region mainly mediated by SST and human population gravity. Our results also suggest that dominant species within small shelf areas share more common traits than dominant species in large areas. This study uncovers previously unknown regional patterns of reef fish functional diversity and provides new insights into how historical, biogeographic, energetic, and anthropogenic factors influence complementary biodiversity facets.